Deglacial upslope shift of NE Atlantic intermediate waters controlled slope erosion and cold-water coral mound formation (Porcupine Seabight, Irish margin) - Wienberg, Claudia; Titschack, Jürgen; Frank, Norbert; De Pol-Holz, Ricardo; Fietzke, Jan; Eisele, Markus; Kremer, Anne; Hebbeln, Dierk (Quaternary science reviews, 2020)
Turbulent bottom currents significantly influence the formation of cold-water coral mounds and sedimentation processes on continental slopes. Combining records from coral mounds and adjacent slope sediments therefore provide an unprecedented palaeo-archive to understand past variations of intermediate water-mass dynamics. Here, we present coral ages from coral mounds of the Belgica province (Porcupine Seabight, NE Atlantic), which indicate a non-synchronous Holocene re-activation in mound formation suggested by a temporal offset of ∼2.7 kyr between the deep (start: ∼11.3 ka BP at 950 m depth) and shallow (start: ∼8.6 ka BP at 700 m depth) mounds. A similar depth-dependent pattern is revealed in the slope sediments close to these mounds that become progressively younger from 22.1 ka BP at 990 m to 12.2 ka BP at 740 m depth (based on core-top ages). We suggest that the observed changes are the consequence of enhanced bottom-water hydrodynamics, caused by internal waves associated to the re-invigoration of the Mediterranean Outflow Water (MOW) and the development of a transition zone (TZ) between the MOW and the overlying Eastern North Atlantic Water (ENAW), which established during the last deglacial. These highly energetic conditions induced erosion adjacent to the Belgica mounds and supported the re-initiation of mound formation by increasing food and sediment fluxes. The striking depth-dependent patterns are likely linked to a shift of the ENAW-MOW-TZ, moving the level of maximum energy ∼250 m upslope since the onset of the last deglaciation.
Gesehen am 25.09.2020